Review of Trigona (Nostotrigona) Engel, 2021 from Brazil with description of three new species (Hymenoptera: Apidae: Meliponini) - Ribeiro, Cristiano Feitosa; Nogueira, David Silva; Oliveira, Favízia Freitas De; Oliveira, Marcio Luiz De (Zootaxa, 2023)
Trigona Jurine, 1807 (Hymenoptera: Apidae: Meliponini) is a Neotropical genus of stingless bees that is most diverse in the Amazon biome. The subgenus T. (Nostotrigona) was recently described and contains the taxa of the T. recursa species-group. In the present study, three new species of this subgenus are described: T. daianeae sp. nov., T. juvenili sp. nov., and T. mandaloriana sp. nov., including new records of T. permodica Almeida, 1992 for Brazil. A distribution map for T. (Nostotrigona) species are also provided.